Temperature-dependent thermodynamic studies of glycols in aqueous solutions of vitamin B3. Issue 1 (1st May 2022) - Chakraborty, Nabaparna; Lamba, Manisha; Juglan, K C; Kumar, Harsh
Abstract: At the variation of temperatures from (293.15 to 308.15) K, the densities and speed of sound for liquid mixtures containing propylene glycol and hexylene glycol in aqueous vitamin B3 (niacin) at (0.01, 0.03, and 0.05) mol·kg -1 concentration has been measured with Anton Paar DSA 5000 M. These experimental data were used to calculate various acoustic and thermodynamic parameters such as intermolecular free length, acoustic impedance, adiabatic compressibility, Wada's constant, Rao's Constant and Vander Waal's constant which gave the insight of the intermolecular reactions inside the ternary mixture of vitamin B3 (Niacin) and glycols (PG/HG).